2012
DOI: 10.1155/2012/574184
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Nucleolus Candidate Zone in White Blood Cells of Peripheral Blood Smear Images Using Curvelet Transform

Abstract: The main part of each white blood cell (WBC) is its nucleus which contains chromosomes. Although white blood cells (WBCs) with giant nuclei are the main symptom of leukemia, they are not sufficient to prove this disease and other symptoms must be investigated. For example another important symptom of leukemia is the existence of nucleolus in nucleus. The nucleus contains chromatin and a structure called the nucleolus. Chromatin is DNA in its active form while nucleolus is composed of protein and RNA, which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Where (̅, ̅) is the coordinate of the center point, (xi,yi) is the coordinate of the pixels with the same label and N is the number of the pixels of a connected component. In former studies, it was shown that in a spindle-shaped object (which is the ordinary shape of a fish), the boundary pixels' distances vary significantly relative to the center of the component [26] [27]. Therefore, if the variation of the boundary pixels' distance with respect to a component center was less than a certain threshold, that component was considered not to be a fish and was eliminated from the frame.…”
Section: Size and Shape Filtermentioning
confidence: 99%
“…Where (̅, ̅) is the coordinate of the center point, (xi,yi) is the coordinate of the pixels with the same label and N is the number of the pixels of a connected component. In former studies, it was shown that in a spindle-shaped object (which is the ordinary shape of a fish), the boundary pixels' distances vary significantly relative to the center of the component [26] [27]. Therefore, if the variation of the boundary pixels' distance with respect to a component center was less than a certain threshold, that component was considered not to be a fish and was eliminated from the frame.…”
Section: Size and Shape Filtermentioning
confidence: 99%
“…Several researchers have proposed many methods to achieve accurate segmentation results. Many researchers used clustering approaches to segment WBC from microscopic images such as K‐means clustering technique in other works, 7–10 and Fuzzy C‐means in the work of Viswanathan 11 . However, a fast and robust segmentation of WBCs still remains a challenging task 12 …”
Section: Introductionmentioning
confidence: 99%
“…Soltanzadeh et al . () extracted nuclei by means of K‐means method and then applied curvelet transform to extract the candidate locations of chromatins and nucleoli. Also, Sarrafzadeh et al .…”
Section: Introductionmentioning
confidence: 99%